Organophosphorus Poisoning: Acute Respiratory Distress Syndrome (ARDS) and Cardiac Failure as Cause of Death in Hospitalized Patients - Ramadori, Giuliano Pasquale (International journal of molecular sciences, 2023)
Industrial production of food for animals and humans needs increasing amounts of pesticides, especially of organophosphates, which are now easily available worldwide. More than 3 million cases of acute severe poisoning are estimated to occur worldwide every year, and even more cases remain unreported, while 200,000–350,000 incidentally or intentionally poisoned people die every year. Diagnostic and therapeutic procedures in organophosphate poisoning have, however, remained unchanged. In addition to several neurologic symptoms (miosis, fasciculations), hypersecretion of salivary, bronchial, and sweat glands, vomiting, diarrhea, and loss of urine rapidly induce dehydration, hypovolemia, loss of conscience and respiratory distress. Within hours, signs of acidosis due to systemic hypoxia can be observed at first laboratory investigation after hospitalization. While determination of serum-cholinesterase does not have any diagnostic value, it has been established that hypoalbuminemia alone or accompanied by an increase in creatinine, lactate, or C-reactive protein serum levels has negative prognostic value. Increased serum levels of C-reactive protein are a sign of systemic ischemia. Protective mechanical ventilation should be avoided, if possible. In fact, acute respiratory distress syndrome characterized by congestion and increased weight of the lung, accompanied by heart failure, may become the cause of death. As the excess of acetylcholine at the neuronal level can persist for weeks until enough newly, locally synthesized acetylcholinesterase becomes available (the value of oximes in reducing this time is still under debate), after atropine administration, intravenous albumin and fluid infusion should be the first therapeutic interventions to reestablish normal blood volume and normal tissue oxygenation, avoiding death by cardiac arrest.